How are children coping with COVID-19 health crisis? Analysing their representations of lockdown through drawings. (November 2022) - Idoiaga Mondragon, Nahia; Eiguren Munitis, Amaia; Berasategi Sancho, Naiara; Picaza Gorrotxategi, Maitane; Dosil Santamaria, Maria
Spain is one of the European countries most affected of COVID-19, and also the one with the most stringent restrictions for children. This study aims to explore how COVID-19 lockdown affects children by analysing 151 drawings from children in lockdown. Findings were represented in four main categories: (1) Activities; (2) Emotions; (3) Socialization; and (4) Academic. The results indicate the need to manage the lockdown situation taking into account also children's voices and by placing greater emphasis on social and inclusive policies to help alleviate the possible effects of the pandemic and the lockdown on them.